Evaluating community engagement efforts in a clinical and translational research initiative - Kelly Finck Waters; Brenda Joly; Carolyn E. Gray; Jan K. Carney; Kathleen M. Fairfield (Journal of Clinical and Translational Science, 2025)
A priority of the Northern New England Clinical and Translational Research (NNE-CTR) Network is conducting, promoting, and advancing community-engaged research through its Community Engagement and Outreach (CEO) Core. We sought to measure the CEO Core’s success in strengthening community-level research partnerships using a validated survey platform based on network science to map and track collaborations over time. The survey was completed by 59/76 organizations (77.6% response rate). Key findings included a high level of trust and a modest level of perceived value relative to published benchmarks. Additional specific findings will inform opportunities to improve the network as the NNE-CTR matures.